Tinjauan Pelaksanaan Family Folder Untuk Rekam Medis Rawat Jalan Di Puskesmas Guntung Payung Tahun 2016 - Rina Gunarti; Zainal Abidin; Mariatul Qiftiah; Bahruddin Bahruddin; STIKES Husada Borneo; Puskesmas Guntung Payung; RS Khusus Bedah Siaga Banjarmasin; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2016)
Family folder is a kind of record-keeping, based on existing areas health facility is located. Storage shelves medical records will be grouped by the name of the existing area. In the medical record storage shelves in primary health Guntung Payung still visible several medical record folders placed in storage shelves that are not in the region should be so the purpose of this research was to know the implementation of the family folder for outpatient medical records in the primary health center Guntung Payung in 2016. The research method using descriptive survey. The unit of analysis of this research that medical records outpatient primary health center Guntung Payung with family folder. Based on the research results, primary health enter Guntung Payung using medical records for data recording and using family folder shaped the form used is BPJS participant statements sheets, the registration sheets and status of the patient sheets. The use of outpatient form primary health centers Guntung Payung not in accordance with Decree No. 269 / Menkes / Per/III / 2008 article 3 poin (1). The numbering system of medical records in the primary health center Guntung Payung is using a numbering system unit. Medical record number assigned use a manual system that is use the registry book. The numbering system of medical records in the primary health center Guntung Payung consists of 8 digits medical record number. Numbering of medical records in the primary health center Guntung Payung is not in accordance with the Budi (2011) that has not been used 6 digits medical record number and the using area code is not in accordance with IFHIMA (2012). Medical records storage system in primary health center Guntung Payung where there are 5 areas primary health center Guntung Payung so that each region has a code of each storage shelves. The storage system in primary health center Guntung Payung complies with Budi (2011) that is using the storage system where storage area medical records will be grouped based on the name of the region but the alignment system of medical records at the storage shelves by using straight numbers in the category of index numbers of medical records).